How Is Research Connecting Artificial Intelligence, Sustainability Governance, and Agri-Food Supply Chains Evolving? A Bibliometric Analysis - Qalbin Salim Fazli; Mussa Isaack Delya; Erick Hironimus Kihwili; Muhammad Qashmal; Iin Shabrina Hilal; Ghalieb Mutig Idroes (Indatu Journal of Management and Accounting, 2025)
This study examines the development of research situated at the intersection of artificial intelligence, sustainability governance, and agri-food supply chains through a comprehensive bibliometric analysis of 988 Scopus-indexed articles published between 2017 and 2025. This time range was selected because scholarly attention to artificial intelligence in sustainability and agri-food systems began to intensify after 2017, alongside the emergence of Industry 4.0, data-driven governance frameworks, and circular economy agendas, allowing the analysis to capture both the formative and consolidation phases of this research domain. A structured search, screening, and eligibility process was applied to ensure thematic relevance and methodological rigor, followed by performance analysis and science-mapping techniques using VOSviewer, CiteSpace, and complementary normalization procedures. The findings reveal accelerating publication growth, concentrated collaboration networks, and thematic convergence around digital sustainability, circularity, and data-driven supply-chain optimization. Keyword and citation structures indicate that the field increasingly integrates technological and environmental perspectives, although research contributions remain unevenly distributed across authors, institutions, and countries. The study highlights the emergence of a more coherent knowledge base while underscoring the need for broader participation and deeper conceptual synthesis. These insights provide a consolidated foundation for guiding future work toward stronger theoretical development and more impactful applications in sustainable agri-food systems.